Новые среднеазиатские виды чехлоносок (Lepidoptera, Соleophoridae), живущих на полынях - Фалькович, М.И. (Вестник зоологии, 1972)
In the Middle Asia 7 species of casebearers are developed on Artemisia, the section Seriphidium. All of them are endemic for a desert zone. Three new species from the Bukhara region are described. Larvae of Coleophora zhusani sp. n. feed on leaves and those of C. polynella sp. n. and C. amentastra sp. n. on generative organs of Artemisia turanica K r a s c h, and related species of wormwood.